MODELS OF ENTREPRENURSHIP DEVELOPMENT IN RURAL TOURISM DESTINATIONS IN VOJVODINA - Jegdić, Vaso; Škrbić, Iva; Milošević, Srđan (Economics of Agriculture, 2017)
The subject of the research in this paper is the development and the application of entrepreneurship in rural tourism destinations. The aim of the paper is to identify key forms of rural entrepreneurship tourism in Vojvodina. General analytic-synthetic method of research was applied, spanning from the bibliographic-speculative to empirical approach. It has been determined that messages, villages as tourist products, ethno-houses, and rural households that provide services of accommodation and food, eco-active tourism, tourism offer of food and drinks produced in the system of organic production, as well as traditional rural events, can be the basis of rural tourism product in Vojvodina. The development of rural tourism should be based on effective investment in the tourism offer through entrepreneurial projects that are in accordance with modern trends of demand. Investment into tourism offer in rural tourism destinations would influence the growth of income made from rural tourism, and therefore, the economic development of those areas.